The meaning of the letter on the meaning in itself according to Ibn al-Nahas (d.698 AH) - Hammoud Arak Al-Qurashi, Mahmoud; Yaqoub Hamid, Ahmed (Journal of College of Education, 2021)
The letter in the language : the edge, the margin , the side and  the boundary. The letter : is the edge of somethingThe letter is everything : its side, its verge , and its boundaryIn  grammar a letter can be defined as : a word that refers to meaningFor example Alhamza for interrogative, ( from An) , ( wish Layta) ,( May be Lala) and  ( but Lakin ) called letters of meaning and grammarians in symbols of letters on the meaning for Ibn Alnahas, the letter refers to the meaning of itself